Communicative language teaching method, to improve the oral-skills in learning English as a foreign language - Guanoquiza Gallardo, Cinthia Jomaira (2022)
Oral skills are always seen as the main ability to develop when someone is learning a new language. This project analyzed the strategies of Communicative Language Teaching method (CLT) to develop the oral skills of English as a foreign language in the teaching-learning process. A group of 29 students in the Eighth grade at Naciones Unidas School participated in the project. Mixed method was applied. Qualitative research was used initially with a pretest to comprehend the problematic. Then, Quantitative phase was applied with an online survey using a Likert scale to obtain quantifiable data on the (CLT) strategies in the teaching-learning process of the English language oral skills. The pretest results showed that students of elementary School had problems in the production of the speech and its sub skills such as fluency, accuracy, and pronunciation. Then, the survey results showed that various strategies of the CLT were advantageous to improve the students’ oral skills such as dialogue, group work, role play, opinion sharing and dramatization. Furthermore, students feel highly inspired when participating in communicative strategies. These strategies permitted to enhance some fluency, accuracy and pronunciation, and students were able to use English in a realistic and communicative task.